Differentiation between stercoral perforation and colorectal cancer perforation - Moon,Ji Yoon (2019)
SUMMARY OBJECTIVE: To determine the computed tomography (CT) signs associated with stercoral perforation and colorectal cancer perforation. MATERIALS AND METHODS: From May 2003 to Feb. 2015, all surgically and pathologically confirmed patients with stercoral perforation (n=8, mean age 68.3 years) or colon cancer perforation (n=11, mean age 66.3 years) were retrospectively reviewed by two board-certified radiologists blinded to the proven diagnosis. The following CT findings were evaluated and recorded for each patient: wall thickness of the distal colon adjacent to perforation site, pattern of the colon wall thickening and enhancement, length of the thickened bowel wall, presence of fecaloma, degree of proximal colon dilatation, and pericolonic inflammation or presence of pericolonic abscess, and number of enlarged pericolonic lymph nodes. These findings were correlated with the pathologic diagnosis. RESULTS: The mean thickness of the distal colonic wall adjacent to the perforation site was 13.6 mm in patients with colorectal cancer perforation and 5.1 mm with stercoral perforation, which was statistically different. There was a significant correlation between colorectal cancer perforation and eccentric wall thickening (p<0.01). CT findings of layered enhancing wall thickening (p<0.01) and the presence of fecaloma in the proximal colon (p<0.01) were significant findings for stercoral perforation. Patients with colorectal cancer displayed more pericolonic lymph nodes (mean 2.27, p<0.05). CONCLUSION: Fecaloma in the proximal colon and layered enhancing wall thickening adjacent to perforation site are likely due to stercoral perforation. Eccentric bowel wall thickening at the distal portion of the perforation site with many enlarged pericolonic lymph nodes is most likely due to colorectal cancer perforation.